Comparison of sensory processing between children with hearing aid and their normal peers in Shiraz City (2019) - Sahar Ghanbari; Ali Reza Jamali (Shiraz University of Medical Sciences, 2021)
Background:  Sensory processing is an important factor in development and affects the function of the senses in daily living activities. Hearing impairment may lead to some difficulties in sensory processing in children with hearing impairment. Objectives:  In this cross-sectional study, the sensory processing of children with hearing impairment and that of their normal hearing peers who were between 3 to 6 years old were compared. Methods: The study population consisted of 60 normal-hearing and hearing-impaired children with hearing aids in Shiraz who were between 3 and 6 years of age. Dunn's Short Sensory Profile was utilized in both groups. The results were statistically analyzed by SPSS 21, and a p-level of < 0.05 was considered significant. Results: Independent t-test results showed that there was no significant difference between the two groups in total sensory processing (p -value = 0.097), touch sensitivity (p -value = 0.043), olfactory and taste sensitivity (p -value = 0.259), movement sensitivity (p -value = 0.079), sensory seeking (p -value = 0.229), hearing processing (p-value = 0.390), low energy and weakness (p-value = 0.916), or hearing and vision sensitivity (p -value = 0.429). The total mean score was 15.28 ± 4.8 for children with hearing aids and 15.28 ± 4.6 for normal-hearing children. Conclusions: The results of this study showed that the impact of hearing impairment on sensory processing is unperceivable and needs to be addressed through more research However, it does seem that hearing impairment may affect one area of sensory processing.